Expression of Folklorisms in the Works of Ghafur Ghulam - Ahmadovich, Hayitov Hamza (European Journal of Life Safety and Stability (2660-9630), 2022)
Ghafur Ghulam wrote in his article "Let's learn from folklore": "Almost all great writers have used and studied folklore ... Folk art - following folklore helps our written literature to enter, popularize and assimilate among the people." first of all, he himself adhered strictly during his multifaceted work. Recognizing that folklore is an inexhaustible treasure, he proved in practice that to be a true folk poet or writer, one must not only know them, but also follow them in order to achieve perfection. Throughout his creative career, he was able to achieve high results based on the principle of learning and following directly from folklore. This is evidenced by the example of poems, stories, narratives, literary anecdotes and praises created on the basis of artistic synthesis of folklore genres, motifs and images used in his poetic and prose works.